PENGARUH KUALITAS PELAYANAN TERHADAP TINGKAT KEPUASAN PEMUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS TADULAKO - Rusdin, Rusdin (Katalogis, 2017)
This study aimed to determine the partial and simultaneous influence of service quality on library user satisfaction level at the Library Technical Implementation Unit of Tadulako University. The type of this study was explanatory research based on survey approach. This study was carried out at the Library Technical Implementation Unit of Tadulako University. The variables studied were the independent variable of service quality with its five dimensions, namely tangible, reliability, responsivenes, assurance dan empathy; and the dependent variable of user satisfaction level. The samples of this study amounted to 125 respondents of 14.285 population members with random sampling method. The analysis method used was descriptive verificative method using multiple linear regression analysis.The results showed that the dimensions of tangible, reliability, responsiveness, assurance, and empathy simultaneously had significant influence on library user satisfaction level, with the value of Fcount was 33.990at sig. 0.000; the five dimensions had been influencing each other and together contributed library user satisfaction level with different influence levels. Partially, all the dimensions had influence on user satisfaction level with their own relation level cathegories, respectively the dimension of assurance had â€œstrongâ€ relation level, the dimensions of tangible and responsivenes had â€œmiddleâ€ relation level, and the dimensions of reliability and empathy had â€œvery lowâ€ relation level. Therefore, the amount of service quality influence on library user satisfaction level was determined by the dimensions of tangible, reliability, responsivenes, assurance, andempathy. Meanwhile, the value of R = 0,767meant that the model shaped in this study explained that the contribution of tangible, realibility, responsevenes, assurance, and empathyâ€™s influence on satisfaction level of library users when using Tadulako University Library amounted to 76.70% and the rest 23.30% was owned by other variables outside this study. Based on the results, it was advised that in the effort of service quality improvement, the Library needs to notice the dimensions of reliability (x2) and empathy (x5). To other researchers interested in the other factors relating to libary user satisfaction level, there is still 23.30% of other variables.